2012
DOI: 10.1200/jco.2011.36.9348
|View full text |Cite
|
Sign up to set email alerts
|

Minimal Residual Disease Quantification Is an Independent Predictor of Progression-Free and Overall Survival in Chronic Lymphocytic Leukemia: A Multivariate Analysis From the Randomized GCLLSG CLL8 Trial

Abstract: MRD levels independently predict OS and PFS in CLL. Therefore, MRD quantification might serve as a surrogate marker to assess treatment efficacy in randomized trials before clinical end points can be evaluated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
327
0
8

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 416 publications
(345 citation statements)
references
References 50 publications
10
327
0
8
Order By: Relevance
“…17 Achievement of complete response to therapy with no minimal residual disease has been identified as an independent favorable prognostic factor. 18 Until further clinical investigation is complete, it is unknown whether ocaratuzumab will have the same or better efficacy compared with obinutuzumab when used for treatment of CLL.…”
Section: Discussionmentioning
confidence: 99%
“…17 Achievement of complete response to therapy with no minimal residual disease has been identified as an independent favorable prognostic factor. 18 Until further clinical investigation is complete, it is unknown whether ocaratuzumab will have the same or better efficacy compared with obinutuzumab when used for treatment of CLL.…”
Section: Discussionmentioning
confidence: 99%
“…Recent publications of initial therapy of previously untreated patients with CLL have shown that levels of post-treatment residual disease of below 0.01%, 0.01-1%, and over 1% have prognostic significance in terms of both PFS and OS (1,16). Direct comparison of samples at all levels of residual disease showed excellent correlation between the single tube 10-color assay and the 4 tube 4-color ISA assay.…”
Section: Discussionmentioning
confidence: 89%
“…Six patients were analyzed at various time points after reduced intensity allogeneic stem cell transplantation. As outlined in previous studies of CLL, residual disease levels of <0.01%, 0.01-1%, and >1% were taken to indicated levels of residual disease with significantly different prognostic outcomes (1). Normal blood and BM were obtained from bone marrow transplant donors.…”
Section: Patients Treatment Regimens and Samplesmentioning
confidence: 99%
See 1 more Smart Citation
“…The observed eradication of leukemia cells using commercially available methods can be crucial for the decision to complete the therapy. It has been proved that the assessment of MRD is helpful in estimating overall survival (OS), treatment-free survival (TFS) and progression-free survival (PFS), in the context of the treatment [5,19].…”
Section: Minimal Residual Disease In Cllmentioning
confidence: 99%